2020
DOI: 10.1039/d0cc04750c
|View full text |Cite
|
Sign up to set email alerts
|

Transfecting tissue models with CRISPR/Cas9 plasmid DNA using peptide dendrimers

Abstract: There is currently a lack of efficient reagents to transfect cells with large plasmid DNA, which would be enabling tools for gene editing using CRISPR/Cas9 technology. Herein we report the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…The activity of G 2,3 KL-(Leu) 4 in L configuration almost disappeared, meanwhile for G 2,3 KL-diPalmitamide (D) the activity was only slightly reduced in L configuration (Supplementary Figure S1). Our data follow the same trend and findings as previously published studies in which the amino acid chirality did affect the siRNA and DNA delivery [34][35][36].…”
Section: Lipophilic Peptide Dendrimers Surpass Lipofectamine 2000 (L2000) In Transfecting Reporter Cells In Serum-containing Mediasupporting
confidence: 91%
See 1 more Smart Citation
“…The activity of G 2,3 KL-(Leu) 4 in L configuration almost disappeared, meanwhile for G 2,3 KL-diPalmitamide (D) the activity was only slightly reduced in L configuration (Supplementary Figure S1). Our data follow the same trend and findings as previously published studies in which the amino acid chirality did affect the siRNA and DNA delivery [34][35][36].…”
Section: Lipophilic Peptide Dendrimers Surpass Lipofectamine 2000 (L2000) In Transfecting Reporter Cells In Serum-containing Mediasupporting
confidence: 91%
“…For peptide dendrimer complexes to have better defined molecular structures, merging the lipid component and the dendrimer into a single entity was desired. This approach was recently demonstrated to provide highly efficient transfection reagents for siRNA and large plasmid DNA [34,35]. Studies with fluorophore labeled dendrimers and oligonucleotides showed that endosome acidification induces protonation of the low pK a amino termini of the lipidated dendrimers, which releases part of the dendrimer from the nanoparticle.…”
Section: Introductionmentioning
confidence: 99%
“…What many existing transporters have in common is a poor ability to penetrate deep tissue. [1][2][3][4][5][6][7][8][9][10][11][12][13] Besides some remarkable exceptions, [14][15][16][17][18][19][20] this includes also the popular cell-penetrating peptides (CPPs). 7,8 Access to deep tissue is challenging because it requires a balanced combination of transcytosis and release into the cytosol.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Similar to many antimicrobial peptides (AMPs), [12][13][14][15] polymers, 16 peptidomimetics 17 and foldamers, 18 our peptide dendrimers act by a membrane disruptive mechanism, 19 which in our case involves a-helical folding of the amphiphilic dendrimer core in contact with the bacterial membrane. 20 G3KL and T7 possess eight N-termini with a depressed pK a of B6.5 due to multivalency, implying that, as for related transfection dendrimers, 21,22 the number of positive charges strongly increases at acidic pH. 23 We therefore set out to test if their activity might be pH dependent, an effect observed with many AMPs, 24 and which is important since sites of bacterial infections may be acidic (biofilms, skin surface), or basic (chronic wounds).…”
mentioning
confidence: 99%